2018
DOI: 10.1186/s12890-018-0651-3
|View full text |Cite
|
Sign up to set email alerts
|

Symptom prevalence of patients with fibrotic interstitial lung disease: a systematic literature review

Abstract: BackgroundThose affected by advanced fibrotic interstitial lung diseases have limited treatment options and in the terminal stages, the focus of care is on symptom management. However, quantitatively, little is known about symptom prevalence. We aimed to determine the prevalence of symptoms in Progressive Idiopathic Fibrotic Interstitial Lung Disease (PIF-ILD).MethodsSearches on eight electronic databases including MEDLINE for clinical studies between 1966 and 2015 where the target population was adults with P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
58
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(63 citation statements)
references
References 36 publications
2
58
0
1
Order By: Relevance
“…Numerous clinical audits and research studies have confirmed the high burden of skin infections and hypothesized that early treatment may reduce the risk and subsequent morbidity and mortality associated with acute rheumatic fever (ARF), acute post-streptococcal glomerulonephritis (APSGN) and skin related sepsis. 3 There is a gap in our understanding of the overall incidence of complicated skin infections across all age groups.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous clinical audits and research studies have confirmed the high burden of skin infections and hypothesized that early treatment may reduce the risk and subsequent morbidity and mortality associated with acute rheumatic fever (ARF), acute post-streptococcal glomerulonephritis (APSGN) and skin related sepsis. 3 There is a gap in our understanding of the overall incidence of complicated skin infections across all age groups.…”
Section: Introductionmentioning
confidence: 99%
“…2 People with IPF also experience a significant symptom burden with dyspnoea and cough. 3 Despite the terminal nature of the disease, people with fibrotic ILD (f-ILD) are often unaware of their prognosis and unprepared for end-of-life care decisions. 4 While the American Thoracic Society and British Thoracic Society ILD guidelines recommend early palliative care involvement, 1,4,5 some studies from overseas demonstrate that few people with f-ILD access such care and those who do are referred only late at the very end of life.…”
mentioning
confidence: 99%
“…Symptom burden plagues patients with progressive fibrotic interstitial lung disease (PF-ILD) [1]; this symptom burden, in combination with poor prognosis and uncertainty of disease course heavily impacts quality of life, both for patients and family members [2,3]. Patients with PF-ILD are confronted with a wide range of diagnoses and prognoses; some may live many years with a disease that is responsive to treatment, while others with PF-ILD often have a disease trajectory similar to and/or worse than that of lung cancer [4,5].…”
Section: @Erspublicationsmentioning
confidence: 99%
“…Patients suffer common symptoms related to their chronic lung disease which contributes greatly to their morbidity and impacts their quality of life [1]. Symptoms patients most frequently experience include dyspnoea, cough, fatigue, anxiety and depression, and patients experience varying degrees of symptom burden and functional decline as their PF-ILD progresses [1,2].…”
Section: @Erspublicationsmentioning
confidence: 99%
“…Nonproductive cough is a prominent symptom of interstitial lung disease (ILD) [1], and it has been suggested that cough associated with ILD should be assessed in clinical trials [2]. The prevalence of cough has been reported to be as high as 84% in patients with idiopathic pulmonary fibrosis (IPF) [3], 73% in those with scleroderma-related ILD [4], and 83% in those with chronic hypersensitivity pneumonitis (CHP) [5].…”
Section: Introductionmentioning
confidence: 99%